The Novel KV7.2/KV7.3 Channel Opener ICA-069673 Reveals Subtype-Specific Functional Roles in Guinea Pig Detrusor Smooth Muscle Excitability and Contractility - Provence, Aaron; Malysz, John; Petkov, Georgi V. (The Journal of pharmacology and experimental therapeutics, 2015)
The physiologic roles of voltage-gated KV7 channel subtypes (KV7.1–KV7.5) in detrusor smooth muscle (DSM) are poorly understood. Here, we sought to elucidate the functional roles of KV7.2/KV7.3 channels in guinea pig DSM excitability and contractility using the novel KV7.2/KV7.3 channel activator ICA-069673 [N-(2-chloro-5-pyrimidinyl)-3,4-difluorobenzamide]. We employed a multilevel experimental approach using Western blot analysis, immunocytochemistry, isometric DSM tension recordings, fluorescence Ca2+ imaging, and perforated whole-cell patch-clamp electrophysiology. Western blot experiments revealed the protein expression of KV7.2 and KV7.3 channel subunits in DSM tissue. In isolated DSM cells, immunocytochemistry with confocal microscopy further confirmed protein expression for KV7.2 and KV7.3 channel subunits, where they localize within the vicinity of the cell membrane. ICA-069673 inhibited spontaneous phasic, pharmacologically induced, and nerve-evoked contractions in DSM isolated strips in a concentration-dependent manner. The inhibitory effects of ICA-069673 on DSM spontaneous phasic and tonic contractions were abolished in the presence of the KV7 channel inhibitor XE991 [10,10-bis(4-pyridinylmethyl)-9(10H)-anthracenone dihydrochloride]. Under conditions of elevated extracellular K+ (60 mM), the effects of ICA-069673 on DSM tonic contractions were significantly attenuated. ICA-069673 decreased the global intracellular Ca2+ concentration in DSM cells, an effect blocked by the L-type Ca2+ channel inhibitor nifedipine. ICA-069673 hyperpolarized the membrane potential and inhibited spontaneous action potentials of isolated DSM cells, effects that were blocked in the presence of XE991. In conclusion, using the novel KV7.2/KV7.3 channel activator ICA-069673, this study provides strong evidence for a critical role for the KV7.2- and KV7.3-containing channels in DSM function at both cellular and tissue levels.